Keefektifan Media Pembelajaran Scrapbook Terhadap Hasil Belajar Tematik Siswa Kelas V Tema 5 Ekosistem di SD Negeri 1 Getas - Nurrahman, Bagus Taufik; Untari, Mei Fita Asri; Purnamasari, Iin (CV. Supernova Office Stationary and Printing, 2022)
The background that drives this research is the low learning outcomes of thematic 2 subtheme 1 in grade II elementary school students. This is due to the lack of application of learning models that are not monotonous in the learning process.The problems in this study are: (1) The learning process is still dominated by the teacher. (2) The media used has not been varied and in accordance with the material. (3) In addition, students are less active in teaching and learning activities, resulting in low student learning outcomes. The goal to be achieved in this study is to determine the effectiveness of the use of scrapbook learning media on thematic learning outcomes of fifth grade students of SD Negeri 1 Getas. This type of research is quantitative research with quantitative experimental method and uses One Group Pretest Posttest Design research design. The population used is the entire sample of class II for the academic year 2022/2023. Data collection techniques based on observations and student learning outcomes.The results showed an increase in learning outcomes without being given treatment and learning outcomes using scrapbook media experienced differences. This can be proven from the results of classical learning completeness, which is 80% with good criteria and 28 students who complete with the highest score of 100. The percentage of complete student learning outcomes by implementing scrapbook learning media can be seen from the posttest score, which reaches 80% or already more than the percentage provisions, with the number of students who completed 28 and as many as 7 students who did not complete. The results of the cognitive pretest and posttest data showed differences, in the cognitive pretest test as many as 15 students who completed with the highest score of 90 and as many as 20 students who did not complete with the lowest score of 20, the percentage of classical pretest learning completeness reached 43%. While the cognitive posttest value using scrapbook learning media has reached KKM 65 as many as 28 students who completed with the highest score of 100 and 7 students did not complete with the lowest score of 50, the percentage of posttest classical learning completeness reached 80%. So, it can be said that scrapbook learning media can improve the learning outcomes of fifth grade students with the Ecosystem theme at SD Negeri 1 Getas. So it can be concluded that learning by using it can be concluded that it is proven that the effectiveness of scrapbook learning media in improving the learning outcomes of class V students with the Ecosystem theme at SD Negeri 1 Getas is said to have achieved good criteria.